A novel histochemical method for the visualization of thrombin activity in the nervous system. (21st April 2016) - Bushi, D.; Gera, O.; Kostenich, G.; Shavit-Stein, E.; Weiss, R.; Chapman, J.; Tanne, D.
Highlights: We have developed a new histochemical method for visualizing the location of thrombin activity in the nervous system. The topographic distribution of thrombin activity in mouse brain following ischemic stroke is demonstrated. The distribution of thrombin activity is in good correlation with the infarct areas. Focal areas of highly elevated thrombin activity are detected in teased sciatic fibers following crush injury. Abstract: Although thrombin has an important role in both central and peripheral nerve diseases, characterization of the anatomical distribution of its proteolytic activity has been limited by available methods. This study presents the development, challenges, validation and implementation of a novel histochemical method for visualization of thrombin activity in the nervous system. The method is based on the cleavage of the substrate, Boc-Asp(OBzl)-Pro-Arg-4MβNA by thrombin to liberate free 4-methoxy-2-naphthylamine (4MβNA). In the presence of 5-nitrosalicylaldehyde, free 4MβNA is captured, yielding an insoluble yellow fluorescent precipitate which marks the site of thrombin activity. The sensitivity of the method was determined in vitro using known concentrations of thrombin while the specificity was verified using a highly specific thrombin inhibitor. Using this method we determined the spatial distribution of thrombin activity in mouse brain following transient middle cerebral artery occlusion (tMCAo) and in mouse sciatic nerve following crush injury. Fluorescence microscopy revealed well-defined thrombin activity localized to the right ischemic hemisphere in cortical areas and in the striatum compared to negligible thrombin activity contralaterally. The histochemical localization of thrombin activity following tMCAo was in good correlation with the infarct areas per triphenyltetrazolium chloride staining and to thrombin activity measured biochemically in tissue punches (85 ± 35 and 20 ± 3 mU/ml, in the cortical and striatum areas respectively, compared to 7 ± 2 and 13 ± 2 mU/ml, in the corresponding contralateral areas; mean ± SEM; p < 0.05). In addition, 24 h following crush injury, focal areas of highly elevated thrombin activity were detected in teased sciatic fibers. This observation was supported by the biochemical assay and western blot technique. The histochemical method developed in this study can serve as an important tool for studying the role of thrombin in physiological and pathological conditions.